A Critical Discourse Analysis of Sexual Violence Narratives in The Jakarta Post - Az-Zahra, Rahma; Roselani, Ni Gusti Ayu (Lexicon, 2024)
This study examines the representation of sexual assault survivors in 67 articles from The Jakarta Post (2016-2023) using corpus-assisted critical discourse analysis. Employing concordance analysis and sentiment evaluation, the research highlights a notable focus on the ages of victims, particularly teenagers, advocating for victim-centered language in public discourse. The findings reveal shortcomings in sexual and reproductive health services, legal issues faced by teenage victims, and gaps in assistance programs. The study calls for comprehensive support structures and legal reforms to address persistent challenges. Sentiment analysis underscores the deliberate use of negative language, emphasizing the need for objective reporting. Overall, the research emphasizes the importance of unbiased reporting, robust support mechanisms, and legal reforms to address the multifaceted challenges faced by rape victims.